A Bypass in Jasmonate Biosynthesis - the OPR3-independent Formation - Wasternack, Claus; Hause, Bettina (Trends in plant science, 2018)
For the first time in 25 years, a new pathway for biosynthesis of jasmonic acid (JA) has been identified. JA production takes place via 12-oxo-phytodienoic acid (OPDA) including reduction by OPDA reductases (OPRs). A loss-of-function allele, opr3-3, revealed an OPR3-independent pathway converting OPDA to JA.
Keywords: oxidoreduktasy; Cyclopentanes; Oxidoreductases; cyklopentany; Arabidopsis; Oxylipins; oxylipiny